Arrangement of Players Position in Soccer Using the Technique of Naive Bayes - Putra, Gusti Made Trisetya; Rusli, Muhammad (Bina Nusantara University, 2015)
In the modern soccer era, soccer is already considered as an entertainment, even modern soccer already become as an industry or a business that considered can bring a great profit to the club owner. One of the most important factor in building a team is young age soccer player development. Right young age soccer player development method, can be very helpful in establish a good team. A professional team must have acoach, for the first team or junior team. The duties of a coach is determine a right position for soccer player in the game, this duties sometimes make a coach is hard to making a right decision. This research will discussabout how to design a decision support system for determine soccer player using naive bayes technique. Data mining used naive bayes technique for find a prediction for soccer player based on the player skill test result. From this research result, it can be seen that by using decision support system using data mining with naive bayes technique can be help coach performance in determine position for soccer player especially for young age soccer player development so that can help coach in the making right decision effectively and efficiently.